Nanocrystal Inks: Photoelectrochemical Printing of Cu2O Nanocrystals on Silicon with 2D Control on Polyhedral Shapes - Vogel, Y.; Gonçales, V.; Al-Obaidi, L.; Gooding, J.; Darwish, Nadim; Ciampi, Simone (Wiley, 2018)
Here, a printing technology is reported that enables the functionalization of photoconducting materials with an arbitrary user-defined pattern of nanocrystals. Two sets of information can be encoded into the same unit area; control over the polyhedral shape of individual nanocrystals and high lateral resolution (micrometer scale) for large 2D patterns (millimeter scale) of Cu2O that were grown over unstructured amorphous silicon. The key to this new technology is a parallel modulation of both the electrode kinetics at the silicon/electrolyte interface and the light-assisted control of adsorption of halide ions on the growing Cu2O particles. This is achieved using local pixelation of a visible light stimulus by adapting to the field of photoelectrochemistry spatial light modulation more often used in super resolution microscopy. Any user-defined pattern (i.e., any arbitrary bitmap image file or a sequence of images) is converted within seconds into an array of nanoparticles. The process does not rely on the use of physical masks or chemical templating and it is parallel, meaning, for example, that it is possible to guide the exclusive growth of cubic nanoparticles in an area defined at will by the operator, while the neighboring section(s) are being covered exclusively by octahedrons.